Retrofitting plywood cutting machine controller using programmable logic controller (PLC) / Mohd Najib Soroni - Soroni, Mohd Najib (2003)
This thesis present the technique of replacing the conventional relay system with the PLC system by using OMRON CPMIA-40CDR. The control programs employ ladder logic and transform into logic codes via RS232C cable. This will interfaced with the process that does the task of cutting the plywood. The PLC process will be read by QBasic program and then display the process at the screen. Cutting is done using a knife that powered by motor. The size of plywood is according to user selection. This information's are then transfer to decoder to read the rotation of the motor.